Towards Improving Performance of the Construction Industry in Ghana: A SWOT Approach - Boadu Elijah Frimpong; Riza Yosia Sunindijo; Cynthia Wang (Institute of Research and Community Outreach - Petra Christian University, 2020)
The construction industry is the second largest contributor to GDP and a significant driver of economic activities in Ghana. Given the importance of the construction industry in boosting the national economy, it is essential to develop effective strategies to keep improving the performance of the industry. To achieve this aim, this research conducted the strengths, weaknesses, opportunities and threats (SWOT) analysis of the Ghanaian construction industry. Underpinned by the SWOT analysis, strategic recommendations are provided to minimise the weaknesses and neutralise the threats that confront the industry, while taking advantage of the strengths and exploiting the opportunities presented to it. These include investment to facilitate innovation and growth, human resource development, development and enforcement of policy and standards, and conducive procurement practice. The recommendations are expected to provide practical and theoretical directions to the industry’s stakeholders on effective ways to improve the industry’s performance.